2011
DOI: 10.1007/s00540-011-1266-5
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of psychomotor function after total intravenous anesthesia with remifentanil–propofol or fentanyl–propofol

Abstract: Recovery of psychomotor function in TIVA with remifentanil-propofol is faster than that in TIVA with fentanyl-propofol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…These differences might be mainly attributed to the use of fentanyl for analgesia in the study by Magni et al 15 ; in contrast, we selected an ultra-shortacting opioid, remifentanyl, and our patients also had a younger mean age (by 15 years). Although an analysis of early cognitive functions by Magni et al 15 found no differences in recovery functions between patients who received sevoflurane-fentanyl and propofol-remifentanil combinations while undergoing craniotomy for supratentorial intracranial surgery, the findings of many other studies agreed with our finding that anaesthesia with remifentanyl infusion provides an early recovery 16,17 . Kaye et al 13 compared desflurane and isoflurane in the context of neurosurgery and achieved 50% decrease in early recovery and eye opening times in the desflurane group.…”
Section: Discussionsupporting
confidence: 88%
“…These differences might be mainly attributed to the use of fentanyl for analgesia in the study by Magni et al 15 ; in contrast, we selected an ultra-shortacting opioid, remifentanyl, and our patients also had a younger mean age (by 15 years). Although an analysis of early cognitive functions by Magni et al 15 found no differences in recovery functions between patients who received sevoflurane-fentanyl and propofol-remifentanil combinations while undergoing craniotomy for supratentorial intracranial surgery, the findings of many other studies agreed with our finding that anaesthesia with remifentanyl infusion provides an early recovery 16,17 . Kaye et al 13 compared desflurane and isoflurane in the context of neurosurgery and achieved 50% decrease in early recovery and eye opening times in the desflurane group.…”
Section: Discussionsupporting
confidence: 88%
“…The context-sensitive half-life of remifentanil is extremely less than fentanyl [18] . The recovery of psychomotor function after total intravenous anesthesia (TIVA) with remifentanil, which does not use any inhalational agents, was 30–120 min faster than TIVA with fentanyl [19] . Orthognathic patients who were maintained with TIVA with remifentanil had significantly higher pain scores within the first 4 h postoperatively [20] .…”
Section: Discussionmentioning
confidence: 99%
“…A total of 2879 articles were obtained, of which 14 studies [10][11][12][13][14][15][16][17][18][19][20][21][22][23] were found eligible to be included in the systematic review (Fig. 1).…”
Section: Search Resultsmentioning
confidence: 99%